2007
DOI: 10.1029/2006jd007729
|View full text |Cite
|
Sign up to set email alerts
|

Foam droplets generated from natural and artificial seawaters

Abstract: [1] Submicrometer sea salt aerosol (SSA) particles are routinely observed in the remote marine boundary layer (MBL); these aerosols include cloud condensation nuclei and so affect the earth's radiative balance. Here foams designed to mimic oceanic whitecaps were generated in the laboratory using a range of bubbling flow rates and aqueous media: unfiltered seawater, filtered seawater, artificial seawater, and mixtures of filtered and artificial seawater. The number and sizes of dried foam droplets in the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
154
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(175 citation statements)
references
References 88 publications
(227 reference statements)
16
154
5
Order By: Relevance
“…Garrett [1968] found that particle production from foams (created by a fritted tip) increased by up to a factor of 3 when insoluble, monolayer-forming surfactants were added to a bubbling solution. Similar increases in aerosol production from foams have been reported more recently with the addition of oleic acid [Tyree et al, 2007] or diatomaceous bioexudate [Fuentes et al, 2010b] to seawater. In addition, Fuentes et al observed a corresponding shift in the submicrometer size distribution of the generated particles to smaller sizes.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Garrett [1968] found that particle production from foams (created by a fritted tip) increased by up to a factor of 3 when insoluble, monolayer-forming surfactants were added to a bubbling solution. Similar increases in aerosol production from foams have been reported more recently with the addition of oleic acid [Tyree et al, 2007] or diatomaceous bioexudate [Fuentes et al, 2010b] to seawater. In addition, Fuentes et al observed a corresponding shift in the submicrometer size distribution of the generated particles to smaller sizes.…”
Section: Introductionsupporting
confidence: 55%
“…We do not believe that the deficit can be accounted for by the absence in this work of any particular type of particle potentially found in natural sea spray aerosols, such as small organic particles or microgels, since source fluxes measured above artificial seawaters are comparable to those measured above natural seawaters under similar bubbling conditions (OC = 0 mM curve in Figure 7) [Fuentes et al, 2010a;Martensson et al, 2003;Tyree et al, 2007].…”
Section: Comparison With Previous Bubble-produced Aerosol Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Several different methods have been used to generate surrogate marine aerosols within enclosed tanks including pressurized atomizers (Svenningsson et al, 2006;Riziq et al, 2007;Saul et al, 2006;McNeill et al, 2006;Braban et al, 2007;Niedermeier et al, 2008;Taketani et al, 2009), forcing air through glass filters or sintered materials (Cloke et al, 1991;Martensson et al, 2003;Sellegri et al, 2006;Keene et al, 2007;Tyree et al, 2007;Wise et al, 2009;Hultin et al, 2010;Fuentes et al, 2010) and by a plunging water jet (Cipriano and Blanchard, 1981;Sellegri et al, 2006;Facchini et al, 2008;Fuentes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%